Development of Web-based Application for Laboratory Materials and Tools in Orthotics and Prosthetics Study Program - Raden Achmad Candra Putra; Argianto Argianto; Suci Anatasia (Eduvest - Journal of Universal Studies, 2026)
Practicum assignments in the laboratory are an essential component of learning, enabling students to apply theories learned in class to achieve learning objectives. In the Applied Orthotics and Prosthetics Undergraduate Study Program at the Ministry of Health Polytechnic Jakarta I, practicum activities carry greater weight than theoretical instruction. This aims to improve student competence in the management of orthotic and prosthetic devices directly. However, in practice, there are many obstacles to completing practicum activities, resulting in learning outcomes not being optimally achieved. Therefore, the purpose of this research is to develop a web-based application for laboratory materials and tools for the Orthotics and Prosthetics Study Program. The method used follows the Web Development Life Cycle (WDLC), namely planning, analysis, design and development, and functional testing. The results of the study show that the web-based application for laboratory materials and tools in the Department of Orthotics and Prosthetics at Jakarta I Polytechnic can facilitate the documentation of laboratory materials and tools entering and leaving the storage area. The results of black-box functional testing indicate that the system operates well according to the established criteria